U.S.‐India Ties: Calibrating Collaboration Post‐Non‐Alignment. Issue 1 (16th January 2016) - Rajagopalan, Rajeswari Pillai
Abstract : With the rise of India, China, and Japan, the 21st century is often hailed as the Asian century. Whether these states can collaborate with each other over the long‐term in an effort to avoid regional anarchy in the Asia‐Pacific is an open question. How U.S.‐India ties will evolve constitutes a major determinant of how much stability or strife the Asia‐Pacific will experience over the foreseeable future. Selected aspects of this important bilateral relationship will be assessed here. The nature of U.S. grand strategy in Asia, and where India fits in this strategy will be examined. Understanding U.S. grand strategy provides insight to American strategic concerns and their impact on Washington's important bilateral relationships. U.S. and Indian perspectives on grand strategy will then be compared. Finally, how India's grand strategy plays into that country's foreign policy toward the United States relative to overall regional concerns will be evaluated.